Ponticulus posticus: radiographic findings on the posterior arch of the atlas vertebrae – review article - Nagalaxmi, Velpula; Zardi, Faisal; Sangmesh, Mithare; Srikanth, Kondangal (Journal of Stomatology, 2015)
The ponticulus posticus is a bony arch located on the posterior arch of the atlas vertebrae. It lies in relationship with the vertebral artery. The presence of ponticulus posticus on the atlas vertebrae has been associated with cerebrovascular disorders and cervical pain. It can no longer be considered as a rare anomaly and its finding on the lateral cephalogram can be of great importance for the patients, in whom this anomaly is present, as this information can prove beneficial for the diagnosis of head and neck symptoms in later life.